Evaluating the top-bottom and bottom-up community development approaches: mixed method approach as alternative for rural un-educated communities in developing countries - Isidiho, Alphonsus O.; Sabran, Mohammad Shatar (Mediterranean Center of Social and Educational Research, 2016)
This paper is evaluating the two popular community development approaches; the Top-down and the Bottom-up with their divergent differences in application and the influence each has in developmental projects/ programmes. The authors then propose a new model / approach “MIXED METHOD”. The works of John Cohan and Norman Uphoff, Robert Chambers as earlier advocates of participatory development comes to mind as they tried to deviate from the previous and most popular top –down approach. Considering the fact that there has been an argument on the choice of one against the other, this paper proposes the “mixed method” as the most appropriate approach, as a new approach to balance the dichotomy thereby filling the research gap in search of most appropriate community development method. This advocates the application of both methods as there is need for a mix of both top-down and bottom-up for effective community development. This view of mixed method is borrowed from the supportive and effective empirical evidence for the adoption of mixed methods research in recent time. The review of previous articles, books, conference proceedings, and other internet publications were utilized as the methodological approach hence, the study used secondary data. The paper concludes that there should be a systematic blending or mixing of both top-bottom and bottom-up so as to achieve a holistic and appreciable sustainable development that carries every one along.